2019
DOI: 10.1111/jgs.16177
|View full text |Cite
|
Sign up to set email alerts
|

Objective Sleep Duration in Older Adults: Results From The Irish Longitudinal Study on Ageing

Abstract: OBJECTIVE This study assessed the distribution and correlates of objective sleep duration in the older population in Ireland. DESIGN Cross‐sectional study using population‐derived data from wave 3 of The Irish Longitudinal Study on Ageing. SETTING Community‐dwelling adults. PARTICIPANTS Adults, aged 50 years and older, who wore an accelerometer for at least 4 days (N = 1533). MEASUREMENTS Sleep was measured for at least 4 days in 1533 participants using a GENEActiv wrist‐worn accelerometer device. Sleep parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
(111 reference statements)
2
24
0
Order By: Relevance
“…In this study, sleep time in the previous or forthcoming week was approximately 7.1 hours/day, and the difference between weeks was not significant. The total sleep time per day measured by objective devise-based methodology reported in recent studies for older adults were 6.9 37 ) and 7.7 hours/day 38 ) , and the amount of sleep time in this study was similar to previous reports. Additionally, although the reports on total lying time are limited, it was reported that most disabled home-dwelling older adults had total lying time of 11 hours or more 39 ) .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, sleep time in the previous or forthcoming week was approximately 7.1 hours/day, and the difference between weeks was not significant. The total sleep time per day measured by objective devise-based methodology reported in recent studies for older adults were 6.9 37 ) and 7.7 hours/day 38 ) , and the amount of sleep time in this study was similar to previous reports. Additionally, although the reports on total lying time are limited, it was reported that most disabled home-dwelling older adults had total lying time of 11 hours or more 39 ) .…”
Section: Discussionsupporting
confidence: 88%
“…The general pattern includes a winter peak of longer sleep and decreased performance. Reports consistently associate winter months with longer sleep [30][31][32][33][34][35][36][37] and more sleep concerns. 38 An online survey of 2003 adults commissioned by the AASM showed that one-third (34%) of the respondents slept "more than usual" during the winter.…”
Section: Longitudinal Measuresmentioning
confidence: 99%
“…was administered to identify the circadian preference of our participants. MEQ is a 19-item test that also allows subdividing participants into six categories: definitely morning (70-86), moderately morning (59-69), intermediate morning (50-58), intermediate evening (42-49), moderately evening(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and definitely evening(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Sleep is known to be important for maintaining health and wellbeing and continues to remain important as we age (20). A report based on a survey of family carers in Ireland, most of whom had a high care burden (82% caring for 50+ hours per week) showed 62% of these carers regularly got up during the night to provide care (19).…”
Section: Caring and Sleep Disturbancementioning
confidence: 99%
“…Studies-Depression (CESD8) scale(19,20). This validated measurement tool captures the frequency that participants have experienced a variety of depressive symptoms within the past week.…”
mentioning
confidence: 99%